PROBLEMS AND PROSPECTS OF BANK PROJECT FINANCING - А. А. Sysoeva (Финансы: теория и практика)
The development of large-scale long-term investment projects based on project financing is actual in terms of economic instability. As international experience shows, in realization of major investment projects and programs, the main role belongs to banks.The article investigated the project financing as a special type of bank financing; it was analyzed the correspondence between banking operations of project financing in Russia and traditional criteria of identification; identified the major participants of project financing market in the face of commercial banks. The author concluded that the further development of project financing in Russia is hampered as a result of banking and macroeconomic factors. The importance given to the method of investment projects selection, as well as their monitoring as a tool to reduce the negative effect of credit risk.